PDGFRα and CD51 mark human Nestin(+) sphere-forming mesenchymal stem cells capable of hematopoietic progenitor cell expansion - Pinho, Sandra (The Rockefeller University Press, 2013)
The intermediate filament protein Nestin labels populations of stem/progenitor cells, including self-renewing mesenchymal stem cells (MSCs), a major constituent of the hematopoietic stem cell (HSC) niche. However, the intracellular location of Nestin prevents its use for prospective live cell isolation. Hence it is important to find surface markers specific for Nestin(+) cells. In this study, we show that the expression of PDGFRα and CD51 among CD45(−) Ter119(−) CD31(−) mouse bone marrow (BM) stromal cells characterizes a large fraction of Nestin(+) cells, containing most fibroblastic CFUs, mesenspheres, and self-renewal capacity after transplantation. The PDGFRα(+) CD51(+) subset of Nestin(+) cells is also enriched in major HSC maintenance genes, supporting the notion that niche activity co-segregates with MSC activity. Furthermore, we show that PDGFRα(+) CD51(+) cells in the human fetal BM represent a small subset of CD146(+) cells expressing Nestin and enriched for MSC and HSC niche activities. Importantly, cultured human PDGFRα(+) CD51(+) nonadherent mesenspheres can significantly expand multipotent hematopoietic progenitors able to engraft immunodeficient mice. These results thus indicate that the HSC niche is conserved between the murine and human species and suggest that highly purified nonadherent cultures of niche cells may represent a useful novel technology to culture human hematopoietic stem and progenitor cells.